Minority Stress and Stress Proliferation Among Same‐Sex and Other Marginalized Couples. Issue 1 (February 2015) - LeBlanc, Allen J.; Frost, David M.; Wight, Richard G.
<x xml:space="preserve">Abstract</x> Drawing from 2 largely isolated approaches to the study of social stress—stress proliferation and minority stress—the authors theorize about stress and mental health among same‐sex couples. With this integrated stress framework, they hypothesized that couple‐level minority stressors may be experienced by individual partners and jointly by couples as a result of the stigmatized status of their same‐sex relationship—a novel concept. They also consider dyadic minority stress processes, which result from the relational experience of individual‐level minority stressors between partners. Because this framework includes stressors emanating from both status‐based (e.g., sexual minority) and role‐based (e.g., partner) stress domains, it facilitates the study of stress proliferation linking minority stress (e.g., discrimination), more commonly experienced relational stress (e.g., conflict), and mental health. This framework can be applied to the study of stress and health among other marginalized couples, such as interracial/ethnic, interfaith, and age‐discrepant couples.